Corporate Social Responsibility in UAE: A Case Study of Jumeirah Group’s CSR Practices - Noeiaghaei, Nazanin (2009)
In the past decade focus on Corporate Social Responsibilities (CSR), environment and sustainability have been on rise. Modern organizations are supposed to be aware of these issues. Most of the international and multinational companies have many rules and regulations to be compatible with the standard expectations regard environment and ethics. CSR is a more important issue in developed countries therefore in some developing countries multinational companies have realized the importance of CSR in global business platform. All the companies wanting to enter the international trading and business networks have to act responsible regarding environment and society. UAE is a country known for being multinational. Many international companies have opened area offices in UAE. In the past recent years UAE rulers have started realizing the value of CSR in global context. Implementing rules and regulations, organizing seminars and rising awareness are some activities taken by UAE government regarding CSR. Therefore as a developing country in Middle East UAE still has a long way to go to be able to compete with Europe or North America in this regard. UAE is one of the leading countries in Middle East in term of tourism industry. Every year a great number of tourists visit UAE. UAE Tourism industry has a very important role in UAE economy. To remain a tourist attraction spot, UAE tourism industry has to comply with the global standards. Currently demand for eco-friendly and sustainbable hotels is on rise. Therefore there was not much attention to CSR and environment in any of the Middle East countries. Fortunately in the past few years UAE rules have put a stress on the importance of implementation of CSR and environmental rules and regulations to protect the natural resources of the country, support ethics in business transactions and act in accordance with the global standards.